2023
DOI: 10.1097/md.0000000000033996
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of the normal vagus nerve cross-sectional area in the carotid sheath

Abstract: The aim of this article is to utilize ultrasound to evaluate the normal cross-sectional area (CSA)of the vagus nerve (VN) in the carotid sheath. This study included 86 VNs in 43 healthy subjects (15 men, 28 women); mean age 42.1 years and mean body mass index 26.2 kg/m2. For each subject, the bilateral VNs were identified by US at the anterolateral neck within the common carotid sheaths. One radiologist obtained 3 separate CSA measurements for each of the bilateral VNs with complete transducer removal between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In accordance with our results, several prior studies also did not report any relation between VN CSA and the demographic data of healthy subjects. [ 15 , 17 , 19 , 28 ] In patients with diabetes mellitus, VN CSA was also not correlated with patients’ demographic or clinical data in in a previous study. [ 15 ] Furthermore, peripheral nerve CSA was negatively correlated with age but not with other demographic parameters [ 27 ] or with patients’ clinical data.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In accordance with our results, several prior studies also did not report any relation between VN CSA and the demographic data of healthy subjects. [ 15 , 17 , 19 , 28 ] In patients with diabetes mellitus, VN CSA was also not correlated with patients’ demographic or clinical data in in a previous study. [ 15 ] Furthermore, peripheral nerve CSA was negatively correlated with age but not with other demographic parameters [ 27 ] or with patients’ clinical data.…”
Section: Discussionmentioning
confidence: 84%
“…In prior studies using normal subjects, the CSA of the VN has also been reported to be smaller on the left side. [ 17 19 ] The VN is the longest cranial nerve which arises from the brainstem, exiting the medulla below the ninth cranial nerve, and extending through the jugular foramen. [ 20 ] The VN contributes to the parasympathetic control of the cervical and thoraco-abdominal structures.…”
Section: Discussionmentioning
confidence: 99%